A 3D FEM analysis of stress concentrations around two neighboring cylindrical holes in a prestressed rectangular composite plate under bending - Akbarov, S. D.; Yahnioglu, N.; Yesil, U. Babuscu (SPRINGER, 2012)
The effect of initial stress concentrations around two neighboring cylindrical horizontal holes in an orthotropic rectangular simply supported plate is investigated. The plate is loaded by uniformly distributed normal tensile or compressive forces on its two opposite end faces parallel to the longitudinal axes of the holes and by uniformly distributed normal forces on its upper face. The corresponding problem is formulated within the framework of the 3D linearized theory of elasticity and is solved numerically by using the 3D finite-element method. The influence of material and geometrical parameters, interaction between the holes, and initial stresses on the concentration of stresses around the holes is shown and discussed.
Keywords: initial stress; stress concentration; cylindrical holes; composite plate; 3D FEM; CIRCULAR HOLES; STRAIN; Mechanics; Materials Science; Polymer Science